The unusual conformational preference of N1, N5, N10-tri-p-coumaroylspermidine E-Z isomers from the Japanese apricot tree, Prunus mume, for the (ZZZ)-form. (June 2019) - Mori, Shinnosuke; Akamatsu, Miki; Fukui, Hiroshi; Tsukioka, Junko; Goto, Katsumi; Hirai, Nobuhiro
Graphical abstract: Highlights: Three undescribed isomers of N 1, N 5, N 10 -tri- p -coumaroylspermidine were identified. N 1, N 5, N 10 -tri- p -coumaroylspermidine showed a characteristic photoequilibrium ratio. At photoequilibrium, the ( ZZZ )-isomer predominated over the ( EEE )-isomer. The stability of ( ZZZ )-isomer may arise from π/π, CH/π, and OH⋯OC interactions. Abstract: The Japanese apricot tree, Prunus mume (Siebold) Siebold & Zucc. cv. Nanko, bears two types of flowers: those with anthers that fluoresce under UV irradiation, and those that do not. The chemical composition of both types of anthers has been investigated: the non-fluorescent anthers contained eight E - Z isomers of N 1, N 5, N 10 -tri- p -coumaroylspermidine as major constituents; whereas the fluorescent anthers contained only a limited amount of ( ZZZ )-isomer, but relatively large amounts of fluorescent chlorogenic acid, implying the abnormal development of fluorescent anthers. Of these eight E - Z isomers, three were undescribed, and identified as the ( ZEZ )-, ( ZEE )-, and ( EEZ )-forms. Their photoequilibrium ratios were found to be characteristic, wherein the ( ZZZ )-isomer predominated over the ( EEE ). 1 H NMR and NOESY experiments and ab initio molecular orbital calculations indicated that intramolecular T-shaped π/π, CH/π, and OH⋯O = C hydrogen bonding interactions impart an unusual degree of stability to the ( ZZZ )-isomer that is sufficient to overcome various factors that favor the ( EEE )-form.